Diversification of Home Garden with Avocado Trees Planting in The Karst Area of Karangasem Village, Paliyan District, Gunungkidul Regency - Adriana, Adriana; Wibisono, Mochamat Gunawan; Karyanto, Oka; Figyantika, Arom; Sadewo, Wawan (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2024)
Home garden productivity can be enhanced by managing plant diversity, optimizing stand arrangements, and selecting species suited to local land conditions. Avocado trees, in particular, have strong potential to thrive in the karst regions of Karangasem Village, Paliyan, Gunungkidul. Some trees planted spottily by local people in their home garden have been able to bear fruit. The avocado trees have also been grown intensively in the Semanu District, adjacent to Paliyan District. These factors indicate that avocado trees are well-adapted to the local area. To promote optimal growth, stand management should incorporate appropriate silvicultural practices. The objective of this community service program was to increase the tree species diversification of home gardens in Karangasem Village by planting avocado trees by assisting the Forest Farmer Group of Lestari Mulyo, as a potential driving group to the community. In the future, local communities can hopefully establish avocados as a new commodity to help boost household incomes.